How Safe Is Your Playground? Analyzing Soil in Scottish Schools through a University Outreach Project - Willison, Debra; Davidson, Christine M; Scott, Fraser J (Journal of chemical education, 2020)
School pupils often perceive STEM subjects to be challenging; thus, in this project, an interactive, nationwide STEM investigation was designed to stimulate their interest. The “Soils in Scottish Schools” project provided teachers with a flexible package of resources to allow them to enhance the profile and understanding of soil science of their pupils. This package included presentations, experimental procedures, activities, and monthly newsletters which could be adapted to the particular learning environment of their pupils. In the focal point of the project, teachers were supported to encourage their pupils to collect samples from their school ground which were then analyzed for copper, lead, and zinc levels. This year-long project also afforded teachers with the opportunity to develop the pupils’ investigative skills through engagement with experiments in their own classrooms where they could engage with real data.